Clinical manifestations in patients with anti-IFN-γ autoantibodies syndrome and Talaromyces marneffei infection: a prospective cohort study - Hanlin Liang; Siqiao Liang; Siyao Wu; Ni Chen; Xuemei Huang; Qiangxiu Zeng; Yan Ning; Zengtao Luo; Xiaona Liang; Zhiyi He (BMC Infectious Diseases)
Abstract Background Anti-interferon-γ autoantibodies syndrome (AIGAs syndrome) is characterized by disseminated infections involving various pathogens. The clinical manifestations of AIGAs syndrome with Talaromyces marneffei (TM) infection are not yet completely understood. Methods A prospective cohort study was conducted at the First Affiliated Hospital of Guangxi Medical University from January 2021 to February 2024. Patients diagnosed with TM infection were categorized into two groups: AIGAs-positive with TM infection group (Group 1) and AIGAs-negative with TM infection group (Group 2). We analyzed the clinical manifestations, laboratory data, imaging findings, and pathological characteristics of the patients to gain insights into the disease’s clinical features. Results A total of 80 AIGAs-positive patients with TM infection (Group 1) and 23 AIGAs-negative patients with TM infection (Group 2) were enrolled. Disseminated infection was significantly more common among Group 1 patients (P < 0.001). Patients in Group 1 had higher serum G test levels than those in Group 2 (P < 0.001). They also showed higher levels of white blood cells, neutrophils, lymphocytes, eosinophils, monocytes, C-reactive protein, erythrocyte sedimentation rate, serum ferritin, globulin, immunoglobulin (Ig)G, IgE, and IgG4 (P < 0.05). Common infection sites included the lungs, lymph nodes, bones, skin, and blood in Group 1 patients. Coinfections were frequently with cytomegalovirus (CMV) and non-tuberculous mycobacteria (NTM). Among patients with bone involvement, 92.6% had systemic involvement, while 7.14% had localized involvement. Chest CT, bronchoscopy, and pathology presentations were varied. During a mean 26-month follow-up, 63.63% of patients had exacerbations; 44.9% due to reactivation of the original pathogen and 55.1% due to new pathogen infections. The multivariable Cox regression analysis indicated that dyspnea and bloodstream infection are significant risk factors for the exacerbation of AIGAs-Positive Patients with TM Infection (P < 0.05). Conclusions AIGAs-positive patients with TM infection showed elevated inflammatory markers, abnormal immune indices, increased serum G test levels, and disseminated infections involving multiple organs. The most common coinfections were CMV and NTM. Chest imaging, bronchoscopy, and pathological findings can present diversity.